(Dis)Abled Security - Skelnik, Klaudia; Jaskulski, Mariusz (Historia i Polityka, 2025)
According to the Polish legislation, “protection of persons” involves activities aimed at ensuring the safety of life, health, and personal integrity. In the article, the Authors present an analysis of three cases of assassination – the assassination of the first President of the Republic of Poland Gabriel Narutowicz in 1922, the assassination of the assistant of the MEP Marek Rosiak in 2010, and the assassination of the Mayor of Gdańsk Paweł Adamowicz in 2019. In the following part of the article, the Authors present the assassination attempts on Slovak Prime Minister Robert Fico, and US presidential candidate (former US President) Donald Trump, discussing the irregularities that took place during these events. The Authors also point out irregularities in the personal and property protection industry in Poland that require immediate changes, including legal changes in this area. Further downplaying the current situation may result in an escalation of attacks and acts of sabotage in Poland. As a country that has been actively supporting Ukraine since the first days of Russia’s aggression, Poland has been targeted not only by the aggressor but also by other countries, whose interest lie not only in defeating the Ukrainian state but also in instilling a sense of insecurity among the citizens of neighboring countries. The main purpose of this article is not to criticize services and entities dealing with personal protection. The Authors would rather like to point the way to rapid changes aimed at minimizing threats and counteracting the escalation of trends conducive to the occurrence of dangerous situations.